ANALISIS KINERJA PENYULUH PERTANIAN DI KOTA KENDARI - Eko Saputra; Sukmawati Abdullah; Yoenita Jayadisastra; Tjandra Buana (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study was to assess the performance of agricultural extension workers in Kendari City. The population of this study comprised 63 agricultural extension workers in Kendari City. The sample was determined using the saturated sampling method, also known as census, which entailed the inclusion of the entire population. The data were collected using a variety of methods, including observation, a review of the literature, documentation, and interviews guided by questionnaires. The research variables are the performance of agricultural extension workers. The collected data is then subjected to quantitative analysis. The quantitative analysis process was executed by the Work Achievement Value (NPK) formula. The results indicated that the performance of agricultural extension workers in Kendari City was predominantly in the medium or good category, as evidenced by the mean value of the Work Achievement Score (NPK), which was recorded at 84.66. Consequently, agricultural extension workers have effectively implemented the three extension indicators, particularly in the preparation and evaluation stages, as outlined in the Minister of Agriculture Regulation Number 91/Permentan/OT.140/9-2013.